#TITLE_ALTERNATIVE# - KARNA WIJAKSANA (NIM : 22108021), INDRA
Many rocks exposed near Earth's surface show well-defined fabric elements in the form of bedding, stratification, layering, foliation, fissuring, or jointing. In general, these rocks have properties (physical, dynamic, thermal, mechanical, and hydraulic) that vary with direction and are said to be inherently anisotropic. Evaluating anisotropic mechanical properties helps predicting the behaviour of rock materials in analysis, design, and construction, and improves the quality and safety. Elastic constants of anisotropic rocks affect deformation analysis and design in engineering. It is important to estimate the elastic constants of anisotropic rocks, rapidly and accurately. In a previous research, elastic constants of transversely isotropic rocks obtained by indirect tensile test (Brazilian test) and the iterative procedure. Where used four samples of marble from Taiwan. The first sample with the axis perpendicular to the plane of transverse isotropy. Furthermore, the strain values obtained, are used to determine the value of elastic constants E1 and ν1. Another three samples are sample with θ = 15o, 30o, and 45o, in which the axis parallel to the plane of transverse isotropy. Strain values obtained from indirect tensile test (Brazilian test) then used in numerical analysis by back calculation and iterative procedure, to obtain the elastic constants E2, ν2, and G2. This research will be discussed regarding laboratory testing and analytical methods to determine the four values of elastic constants of transversely isotropic rocks. Analytic calculations performed to determine the elastic constants of rock material with the assumption of linear, elastic, homogeneous, and transversely isotropic. In this research, the strain value is determined on the condition of 50% of peak stress on stress-strain curves. Multilinier regression analysis with least squares estimation method used in determining the linear equation to get to the four elastic constants of rock. From the results of uniaxial compression tests, the value depends on the angle between the transversely isotropic plane and the direction of loading, in this case the maximum compressive strength occurs when the load is applied in the direction parallel to the plane of transverse isotropy (θ = 85o). From the analysis conducted on 32 strain measurements, obtained the result that for those rocks, the deformability in the direction normal to their bedding is greater than that parallel to their bedding (E1 > E2).